The Effect of a Growth Mindset Intervention on Mathematics Learning Motivation Among Junior High School Students - Ira Dahlia; Rifqi Farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Learning motivation is a key psychological factor influencing students' engagement and achievement in mathematics. Students with low learning motivation tend to exhibit low self-confidence, avoid challenging tasks, and give up easily when faced with difficulties. One psychological approach that has shown promise in addressing this issue is the Growth Mindset Intervention, which encourages students to believe that intelligence and abilities can be developed through sustained effort, effective learning strategies, and continuous practice. This study aimed to examine the effect of a Growth Mindset Intervention on mathematics learning motivation among junior high school students. A quantitative approach with a pre-experimental One-Group Pretest–Posttest Design was employed. The participants consisted of 10 students from SMP Bina Negara Baleendah, Indonesia, selected through purposive sampling. Mathematics learning motivation was measured using a Likert-scale questionnaire administered before and after the intervention, and the data were analyzed using the Wilcoxon Signed-Rank Test. The results showed that the mean mathematics learning motivation score increased from 54.00 at pretest to 84.50 at posttest. Statistical analysis revealed a significant difference between pretest and posttest scores (Z = −2.823, p = .005), with a very large effect size (r = .89), indicating that the intervention had substantial practical significance. These findings suggest that the Growth Mindset Intervention is effective in enhancing junior high school students' motivation for mathematics learning by fostering adaptive beliefs about the malleability of mathematical ability. Therefore, integrating growth mindset-based psychological interventions into mathematics education may serve as an effective strategy for promoting students' motivation and engagement in learning